2020
DOI: 10.1111/ijlh.13363
|View full text |Cite
|
Sign up to set email alerts
|

Falsely decreased FVIII activity following pneumatic tube transport

Abstract: Introduction The pneumatic tube system (PTS) is widely used for sample delivery. We aimed to investigate the impacts of PTS on hemostasis assays. Methods Triplicate samples from 30 healthy volunteers were delivered to the core laboratory manually by human courier or via the 500 m long‐distance PTS or via the 1000 m long‐distance PTS. Comparisons of 19 hemostasis tests were conducted. Results Although PT, INR, APTT, FII, FV, FVII FIX, FX, FXII, DD, α2‐PI, and PC had statistical significance (all P < .05), all h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…However, our results showed that for the delivery of FFP or cryoprecipitate, there was no significant difference in the value of routine haematology and coagulation parameters, including PT, PT‐INR, APTT, TT and FIB, between the specimens tested before and after RLTS transport. In addition, several labile coagulation factors, such as FVIII and FV, have half‐lives that are sensitive to PTS transportation conditions [23]. In contrast, our results showed no significant impact of RLTS transport on FVIII activity results.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, our results showed that for the delivery of FFP or cryoprecipitate, there was no significant difference in the value of routine haematology and coagulation parameters, including PT, PT‐INR, APTT, TT and FIB, between the specimens tested before and after RLTS transport. In addition, several labile coagulation factors, such as FVIII and FV, have half‐lives that are sensitive to PTS transportation conditions [23]. In contrast, our results showed no significant impact of RLTS transport on FVIII activity results.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, several labile coagulation factors, such as FVIII and FV, have half-lives that are sensitive to PTS transportation conditions [23].…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted by Wang et al (2020), the ndings regarding the hemolysis rate showed one hemolyzed sample from a 500m-PTS group and a 40% hemolysis on samples from the 1000m-PTS group. Supplementarily, Nybo (2018) indicated an increase in the Hemolysis Index for most types of PTS stated in the study.…”
Section: Hematologymentioning
confidence: 94%